Identification of Compounds With Vasoactive Properties in a Pitaya Juice Extract (Stenocereus griseus) - Rodríguez, Yadira Ramírez (Curr Dev Nutr, 2021)
OBJECTIVES: The objective of this study is to identify the vasoactive compounds present in the pitaya juice extract (PJE) and evaluate its effect using in vivo and in vitro models. METHODS: First, the pitaya juice was obtained from the fruit of Stenocereus Griseus, centrifuged to obtain PJE. Six hundred mL of PJE was frozen until its use and other 600 mL was lyophilized and stored. The lyophilized PJE was analyzed by HPLC-PAD. The wavelengths for detection in the PAD system were 535 and 480 nm for betalains, and 370 and 280 nm for phenolic compounds. On the other hand, the vasoactive effect of PJE was evaluated in isolated rings of thoracic aortas, with (n = 5) and without endothelium (n = 5), of male Wistar rats (250–350 g) previously contracted with phenylephrine (10 mM to 10 μmol/L), followed by the administration of a concentration of 20 mg/mL of lyophilized PJE and 1 mL physiological solution, as a control (30 min of treatment). RESULTS: The profiling of lyophilized PJE by HPLC-PAD showed 16 types of betalains and 31 types of phenolic compounds, which will be analyzed by mass spectrometry. Isolated aortic rings (in presence and absence of the endothelium) administered with PJE showed 8-fold greater vasodilation compared to the control (54.3% ± 14.1 vs 6.7% ± 3.7), suggesting that the compounds present in the PJE may exert a vasodilator effect, of which its action mechanism will be investigated. CONCLUSIONS: Pitaya juice extract contains vasoactive compounds such as betalains and phenolic compounds, which could be responsible for PJE exerting a vasodilator effect that was observed in assays of isolated rat aortic rings. FUNDING SOURCES: 1. Consejo Nacional de Ciencia y Tecnología (CONACYT) 2. Instituto Potosino de Investigación Científica y Tecnológica A.C. (IPICYT).